Optimization of cultivation parameters for bovine respiratory syncytial virus strain Vologda/2019 - V. V. Kirpichenko; S. V. Kononova; I. N. Shumilova; A. A. Nesterov; M. V. Turkova; Ye. A. Bukhon; D. V. Romenskaya; A. V. Sprygin; B. L. Manin; O. P. Byadovskaya (Ветеринария сегодня)
There are currently many controversial issues in the study of bovine respiratory syncytial infection. In this regard, it is relevant to study the biological properties of the virus, optimize the methods of its cultivation and select the most technologically advanced methods of designing diagnostic and prevention tools for this disease. The aim of this work was to select sensitive cell systems and to optimize the cultivation parameters in selected cell cultures. The Vologda/2019 strain of the bovine respiratory syncytial infection virus isolated from biological material obtained from a calf with respiratory symptoms was used in the experiment. The strain was adapted to the continuous cell culture derived from bovine turbinate tissue (BT) and deposited in the State collection of microorganism strains at FGBI “ARRIAH”. It was established that the continuous cell lines of fetal bovine trachea (FBT) and calf kidney (RBT) are the most sensitive cell systems for the reproduction of the bovine respiratory syncytial virus strain Vologda/2019, the maximum accumulation of the virus was observed in these cell cultures. The cytopathic activity of the virus in the FBT cell culture ranged from 4.78 ± 0.18 to 5.50 ± 0.16 lg TCID50/cm3, and in the RBT cell culture – from 4.00 ± 0.23 to 4.75 ± 0.20 lg TCID50/cm3 at days 4–5 of cultivation. It was determined that in case of multiplicity of inoculation of FBT and RBT cell cultures with the virus at 0.1 lg TCD50/cell and the use of 2% glutamine in the maintenance nutrient medium, as well as 2% horse or cattle blood serum, it is possible to obtain virus material with high cytopathic activity.